Electronic, Magnetic and Optical Properties of Disordered Graphene Quantum Dots - Altıntaş, Abdulmenaf; Güçlü, Alev Devrim (Izmir Institute of Technology, 2018)
In this thesis, we theoretically investigate electronic, magnetic and optical properties of disordered graphene quantum dots. The numerical calculations are performed using a combination of tight-binding, mean-field Hubbard and configuration interaction methods. We focus on the effects of long-range disorder and electron-electron interactions on the optical properties and the effects of atomic defect related short-range disorders and electron-electron interactions on Anderson type localization and the magnetic properties of hexagonal armchair graphene quantum dots. For the case of long-range disorder, we show that, when the electron-hole puddles are present, tight-binding method gives a poor description of the low-energy absorption spectra compared to meanfield and configuration interaction calculation results. As the size of the graphene quantum dot is increased, the universal optical conductivity limit can be observed in the absorption spectrum. When disorder is present, calculated absorption spectrum approaches the experimental results for isolated monolayer of graphene sheet. On the other hand, for the case of short-range related disorder, we observe that randomly distributed defects with concentrations between 1-5% of the total number of atoms leads to electronic localization alongside magnetic puddle-like structures. We show that localization length is not affected by magnetization if there is an even distribution of defects between the two sublattices of the honeycomb lattice. However, for an uneven distributions, localization is found to be significantly enhanced.

Bu tezde, düzensiz grafen kuantum noktalarının elektronik, manyetik ve optik özelliklerini inceliyoruz. Nümerik hesaplar tight-binding, mean-field Hubbard ve konfigürasyon etkileşimi metodlarını kullanarak yapılmıştır. Grafen kuantum noktaları için uzun-mesafe etkili düzensizliklerin ve elektron-elektron etkileşimlerinin optik özellikleri üzerindeki etkisi ve atomik-boyutlu kısa mesafe etkili düzensizliklerin ve elektronelektron etkileşimlerinin Anderson tipi lokalizasyon ve manyetik özellikler üzerindeki etkisine odaklanıyoruz. Uzun-mesafe etkili düzensizlikler durumu için, elektron-hole puddlelları olduğu zaman tight-binding metodu, düşük enerjili emilim spektrumu için, mean-field Hubbard ve konfigürasyon etkileşimi metodları ile kıyaslandığında yeterli bir açıklama veremediğini gösteriyoruz. Grafen kuantum noktasının büyüklüğü arttıkça, emilim spektrumunda evrensel optik iletim limiti gözlemlenebiliyor. Düzensizlikler olduğu zaman, izole grafen tabakası için hesaplanan emilim spektrumu deneysel sonuçlarla uyumlu hale geliyor. Diğer taraftan, kısa mesafe etkili düzensizlik durumları için, toplam atom sayısının %1-5 oranı kadar olarak rasgele dağıtılan düzensizlik yoğunluğunun, elektronik lokalizasyonun oluşması yanında manyetik puddle benzeri yapıların oluşmasına neden oluyor. Eğer düzensizlikler alt örgüler arasında eşit bir şekilde dağıtılırsa lokalizasyon uzunluğunun manyetikleşmeden etkilenmediğini gösteriyoruz. Tam tersine, eğer düzensizlikler alt örgüler arasında eşit olmayan bir şekilde dağıtılırsa, lokalizasyonun daha fazla olduğu gözlemleniyor.
Düzensiz Grafen Kuantum Noktalarının Elektronik, Manyetik ve Optik Özellikleri
Thesis (Doctoral)--Izmir Institute of Technology, Physics, Izmir, 2018
Includes bibliographical references (leaves: 58-70)
Text in English; Abstract: Turkish and English
Keywords: Quantum dots; Graphene quantum dots; Meanfield Hubbard